Integrasi Artificial Intelligence dalam Talent Management: Tantangan dan Peluang Menuju Ekosistem Ekonomi Global - Lubis, Dewi Shinta; Adrianto (ARBITRASE: Journal of Economics and Accounting, 2025)
Digital transformation through the adoption of Artificial Intelligence (AI) has become a highly strategic issue in human resource management, particularly in the context of talent management systems. This study aims to analyze the influence of perceptions toward AI, organizational readiness, and digital competency of human resources on the effectiveness of talent management in the industrial sector in Medan City. The research employed a quantitative approach with a survey method, involving 120 respondents consisting of managers and human resource staff in technology and manufacturing companies. Data analysis was conducted using multiple linear regression to examine the causal relationships between variables. The results indicate that the three independent variables simultaneously have a significant influence on the effectiveness of talent management, with a coefficient of determination (R²) of 64 percent, suggesting that these variables explain the majority of the variability in talent management effectiveness. Partially, digital competency proved to be the most dominant factor affecting talent management effectiveness, followed by perceptions toward AI and organizational readiness. These findings affirm that the successful integration of AI in talent management is highly influenced by the organization’s technological readiness as well as the quality and capability of human resources in optimally utilizing digital technologies. The study recommends that organizations prioritize strengthening digital competencies through intensive training and enhancing internal organizational readiness in terms of infrastructure and digital culture, in order to strategically optimize AI utilization. This step is considered crucial in building a competitive and adaptive economic ecosystem in the global digital era. Thus, this study not only provides empirical contributions to the literature on technology-based human resource management but also offers practical implications for organizational policymaking in facing digital transformation.